Prevalencia y factores de riesgo de Hepatitis B y C en donantes de sangre del Hospital Sub Regional de Andahuaylas durante el periodo 2012 - 2016 - Campos Dominguez, Yanet Marisol (2019)
Infection with the hepatitis B and C virus continues to be a public health problem with high mortality and worldwide distribution, with an estimated 2000 million people infected. Peru is considered as an area of intermediate endemicity for HBV with average prevalences of 1-2% for HBsAg and 20-30% for anti-HBcAg. In the Peruvian highlands, some inter-Andean valleys of the eastern slope of the Andean mountain range such as Abancay and Huanta are considered hyperendemic regions due to the high rates of HBsAg carriers. The purpose of this work is to estimate the prevalence and determinants of Hepatitis B and C virus. With the results obtained, we intend to collaborate in the development of useful epidemiological surveillance plans in our environment. The main objective was to determine the prevalence and risk factors of hepatitis B and C in blood donors of the Sub-Regional Hospital of Andahuaylas from 2012 to 2016. A quantitative, observational and cross-sectional study was conducted; and the participants of the study were 3306 donors who went to the Blood Bank of the Sub-Regional Hospital of Andahuaylas, during the years of 2012 to 2016. The determining factors studied corresponded to age, sex, marital status, blood group, HR factor, and other variables of risky sexual behavior. The prevalence found in donors of the Subregional Hospital of Andahuaylas was 0.91% for HbsAg; 15.7%; for HbcAb and 1.1% for Hepatitis C during the period 2012 to 2016. In all the evaluations, no relationship was found between Hepatitis B and C infection with the factors studied; It is necessary to formulate new research to identify other factors that are at risk in the donors of the Blood Bank of the Subregional Hospital of Andahuaylas, as well as to improve the donor registration system.